Relationship between Community Reading Facilities and Adolescent Cultural Literacy at Taman Baca Tanah Ombak in Padang City - Az-zahra, Nadya; Arini, Fitri Dwi (Universitas Negeri Padang, 2025)
The low level of cultural literacy among adolescents in Padang City is an issue that needs attention, especially because of the lack of understanding and appreciation of local cultural values. Tanah Ombak Reading Park as one of the community reading facilities has a strategic role in improving adolescent cultural literacy. This study aims to analyze the relationship between the use of community reading facilities at Tanah Ombak Reading Park and the level of adolescent cultural literacy. This study uses a quantitative, correlative approach method. The research data were obtained through a questionnaire distributed to 20 adolescent respondents who routinely accessed the reading facilities at Tanah Ombak Reading Park in Padang City. The results of the analysis showed a significant relationship between the use of community reading facilities and adolescent cultural literacy. The study found that the frequency of adolescents in utilizing reading parks was relatively low. The frequency of adolescents utilizing reading facilities is directly proportional to their cultural literacy, especially kato nan ampek. This finding confirms that community reading facilities have an important contribution in supporting the development of cultural literacy and encouraging active involvement of adolescents in preserving local culture.